Advancements in metal additive manufacturing: In-situ heat treatment of aluminium alloys during the laser powder bed fusion process - Schimbäck, D.; Kaserer, L.; Mair, P.; Mohebbi, M. S.; Staron, P.; Maier-Kiener, V.; Letofsky-Papst, I.; Kremmer, T.; Palm, F.; Montes, I.; Höppel, Heinz Werner; Leichtfried, G.; et al. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2024)
The high design freedom of laser powder bed fusion (LPBF) additive manufacturing enables new integrated structures, which in turn demand advances in the process conditions and material design to exploit the full potential of this process. A computational multi-scale thermal simulation and metallurgical analysis of the aluminium alloy Scalmalloy® were used to develop and present a specific process window to enable an in-situ heat treatment during LPBF. High resolution analysis and synchrotron experiments on specimens manufactured in this process window revealed a major proportion of nano-sized Al3(ScxZr1−x) solute-clusters were already present in the as-built state, as predicted by simulation. Supported by this experimental research, the new processing concept of in-situ heat treatment yielded the highest recorded strength values combined with high ductility directly after LPBF for Scalmalloy®. This advancement in LPBF enables highly complex, thin-walled structures directly made from a high-strength, lightweight material, which is not possible with conventional processes that require a subsequent heat treatment cycle.
CRIS-Team Scopus Importer:2024-06-07